(untitled) (Al-Academy, 2016)
This research aim at finding out the impact of using the strategy of shape V on the achievement of the students of the Department of Artistic Education in the subject of "Principles of scientific Research ". This strategy is one of the cognitive strategies used in this topic . To verify the aim of the research ,the two researchers have put the following null hypothesis:-There are no significant differences on the level of 0,05 among the average degrees of the students of the experimental group in their answers on the topics of the pre and post cognitive achievement tests of the subject of "principles of scientific Research " . The two researchers have adopted the experimental approach which consists of one group . the population of the research is restricted by the students of the third stage Department of Artistic Education College of Fine Arts. The sample consists of 12 students selected randomly . To measure the impact of the strategy of shape V on the achievement of students , A cognitive achievement test for measuring the information acquired by student , has been made . the tool of the research has been submitted to the procedures of reliability and discrimination. The two researchers have used ( Wilcox on signed rank test) to show the differences among the group’s students who apply to the experiment (earlier & later). Coefficient of Variation and determination is used to analyses the topics of the cognitive achievement test . In addition , Kuder-Richardson Formula 20 is adopted to state to check the consistency of measurements . The two researchers have drawn the following conclusions :-1– The strategy of shape V has showed an obvious positive impact on the achievement of the students of the Department of Artistic Education in the subject of (principles of scientific Research ).2-The strategy of shape V has contributed in motivating students to participate effectively in the lecture to follow its contents .3-Teaching with the strategy of shape V breaks boredom & inactivity , which reflects positively on the results . According to the conclusions , the two researchers have suggested the following recommendations :-1– Confirming on the use of the strategy of shape V in teaching the subject of (principles of scientific Research ) because of its effect on achieving the goals of the subject .2-Adding the strategy of shape V to the methods of teaching’s systems and training students on teaching it .3-Training Arts teachers on using innovative methods especially the strategy oh shape V .The two researchers also suggest the following :-1– Studying the impact of the strategy of shape V on the achievement of students in other subjects.2–Studying the impact of the strategy of shape V on acquiring artistic concepts of student of the Department of Artistic Education.